(3QSGdI aj GYeGQ GdCOhjI GdeaQOI hGdeQcHIs - (3GdQfOj GdCfOdSjs
(3ChdgG (B:s
(3eaQO GdGOhjI KdGKI CLfGS (B: (3eYOfjI hMjhGfjI hfHGJjI aGdeYOfjI JNJda CYeGQgG hCMhGdgG HMSH TQagG cGdPgH hMLQ GdCdeGS hGdReQO s
(3BNQgG (B:s
(3hCeG GdbQhf hGdMhGai hGdCXdGa aJHbi dCYhGe, hGdNfOHjO jHbi YTQ Sfjf hGddg GYde s
(3GfXQgG eY GdeQTO Qbe (B"730"s
(3fSNI ecQQI ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B103 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(1568) s
Keywords: (3GdWHs